ChemInform Abstract: Silver(I)‐Catalyzed Iodination of Arenes: Tuning the Lewis Acidity of N‐Iodosuccinimide Activation. Issue 25 (June 2016) - Racys, Daugirdas T.; Sharif, Salaheddin A. I.; Pimlott, Sally L.; Sutherland, Andrew
Abstract: A general method for the iodination of a wide range of arenes is developed.